PERAN HAK KEKAYAAN INTELEKTUAL DALAM MEMBINA INOVASI DAN IMPLIKASI HUKUM BAGI BADAN USAHA - I Wayan Suarjana (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
In the era of globalization and rapid technological advances, innovation is the key to success for business entities in various sectors. Intellectual Property Rights (IPR) have an important role in encouraging and protecting innovation. This research aims to get to know more deeply about the role of IPR in fostering innovation and the legal implications associated with it are very important. This research is a type of literature review research that seeks theoretical references related to the cases or problems found. The results of this study can be seen that Intellectual Property Rights play an important role in the legal implications for business entities. Intellectual property rights have an important role in a business, because they can protect and increase consumer confidence in a product from the company.